Community and population health - Green, Lawrence W. (WCB/McGraw-Hill, 1999)
Community health has evolved at the intersection of many disciplines and sectors working locally or regionally. Their common purpose has been to blend the influences of public health, school health, occupational health, social and recreational services, mass health, housing, transportation, self-care, and mutual aid in the service of whole populations.